2018
DOI: 10.1007/s00192-018-3609-3
|View full text |Cite
|
Sign up to set email alerts
|

Does vaginal delivery cause more damage to the pelvic floor than cesarean section as determined by 3D ultrasound evaluation? A systematic review

Abstract: Vaginal delivery was associated with a higher number of LAM injuries, puborectalis defects, increased bladder neck mobility, and enlargement of the hiatal area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…The influence of mode of delivery on occurrence of PFD is still uncertain, but studies in women in general show that cesarean section appears to protect against these symptoms, and vaginal delivery is highly associated with pelvic floor injury. 19 , 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of mode of delivery on occurrence of PFD is still uncertain, but studies in women in general show that cesarean section appears to protect against these symptoms, and vaginal delivery is highly associated with pelvic floor injury. 19 , 20…”
Section: Discussionmentioning
confidence: 99%
“…In women in general, vaginal delivery has been considered the main contributing factor for the development of PFD; however cesarean delivery is not shown as the best choice for the prevention of these symptoms in addition to the health risks for both fetus and mother. 19 , 20…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal birth-induced pelvic floor muscle and nerve avulsion, connective tissue rupture, and nerve compression are strongly implicated in the pathogenesis, development, and progression of UI. [4][5][6][7] Failure to resolve pelvic floor injury following vaginal birth trauma/injury leads to persistent postpartum SUI often worsening with advancing age. 3 The most commonly performed surgical repair techniques for SUI are implantation of synthetic mesh midurethral slings in women.…”
Section: Impact Statementmentioning
confidence: 99%
“…However, our review article showed no difference between bladder neck hypermobility and delivery route. 15 PFDs seem to be closely related to vaginal delivery, especially cases of instrumental delivery. Cesarean section is associated with a reduction in the risk for PFDs, although the routine performance of this procedure does not eliminate the risk for dysfunctions because the pathophysiology is multifactorial.…”
mentioning
confidence: 99%